The Synthesis, Structural Characterization and Superconductivity of $FeSe_x$ with $0.80 ≤ x ≤ 1.20$ (Journal of Atomic and Molecular Sciences, 2012)
We have performed a detailed study on the synthesis, the characterization of structural phases and superconductivity of the binary $FeSe_x$ system from the $Fe$-rich phase into the $Se$-rich phase with $0.80 ≤ x ≤1.20.$ The results indicate that by long-time low-temperature annealing, single phase sample could be obtained near the composition of $FeSe_{0.95}$ with the tetragonal PbO-type structure, while impurities of $Fe$ or $Fe_7Se_8$ would appear if Fe enriched or $Se$ enriched in the starting composition respectively. Bulk superconductivity was found to exist in highly $Se$ deficient phase, but not the single phase, and superconductivity is very sensitive to the $Se$ vacancy content. The anomalous downturn of resistivity around 100 K was eliminated in Se-rich phase, along with the suppression of the main superconducting phase.